Carga poluidora difusa na água e nos sedimentos de sub-bacia do Arroio Cadena - Santa Maria/RS - Santos, Sizabeli Amaral dos (2014)
Economic development and growth of productive activities have been accelerating the degradation of water resources. This research aimed to evaluate the pollutant loads in surface waters and in sediments conveyed by urban drainage systems in a tributary of the Cadena creek in the municipality of Santa Maria-RS. A number of factors may interfere with the water pollution, such as precipitation, stream flow, use and occupation of the land area of the basin, and dry period prior to the event. Results showed that the mean concentration of events presented a variability related to precipitation and precipitation intensity. The average concentration of pollutants in the events tended to increase with the precipitation and precipitation intensity. The prior dry period was significantly correlated with the heavy metals copper and nickel. Diffuse load obtained for total suspended solids, BOD and total coliform organisms was 28.812 kg/ha/year, 3.225 kg/ha/year and 5,03E+07 organisms/ha/year, respectively. The curves M(V) along with the curves of maximum divergence evidenced the variability of the first flush and the differences between the events and parameters. The difference in the pollutant load is due to the high degradation process because of anthropogenic activities, such as urbanization and launch of domestic wastewater. Concentrations of heavy metals in bottom and suspended sediments were below the limit established by CONAMA Resolution 454/12 and the guidelines of the sediments of the Environment Institute of Canada. The bed material of the Cancela-Tamandaí creek is sandy with a predominance of coarse and medium sand.